STUDY OF THE STABILITY OF ?-AMYLASE STRUCTURE OF BACILLUS AQUIMARIS MKSC6.2 WITH TEMPERATURE AND CONCENTRATION NACL VARIATIONS USING MOLECULAR DYNAMICS SIMULATION - Gabriella Hutagalung, Christy
?-Amylases derived from Bacillus aquimaris MKSC6.2 (BaqA) belong to the new subfamily of Glycosyl Hydrolase (GH13) enzymes. BaqA has the ability to degrade raw starch in the absence of SBD (Starch Binding Domain). The amount of ?-amylase which has activity in degrading raw starch in the absence of SBD is 10% of the total number of enzymes that have been characterized. ?-Amylase BaqA expressed in Escherichia coli BL21DE3 is known to form inclusion bodies or precipitate. The cutting of 34 amino acid residues at the C end of ?- amylase BaqA (BaqA?C) that has been carried out previously succeeded in obtaining ?- amylase BaqA?C which is soluble in buffer solution. This study aimed to examine the effect of cleavage 34 amino acid on protein structure using a molecular dynamics simulation approach. BaqA which has been minimized and equilibrated in the preparation process will be simulated under system conditions where the temperature, pressure, and salt concentration have been adjusted. Simulations carried out for 100 ns showed that the BaqA?C structure was relatively more stable at high temperatures and concentrations than BaqA. RMSD and radius of gyration analysis showed that the residues in BaqA were much more volatile than BaqA?C. The removal of hydrophobic amino acids in BaqA also did not result in the loss of the halostability properties of BaqA. The two proteins (BaqA and BaqA?C) did not experience structural damage at high salt concentrations (2 M) as seen from the visualization results. The simulation results prove that truncation of 34 amino acids at the C end can increase the thermostability and halostability of BaqA?C and make the protein structure of BaqA?C more compact.